Prehospital stroke mimics in the Stockholm Stroke Triage System - Sjöö, Mimmi; Berglund, Annika; Sjöstrand, Christina; Eriksson, Einar E.; Mazya, Michael V. (Frontiers in Neurology, 2022)
Introduction In 2017, Stockholm implemented a new prehospital stroke triage system (SSTS) directing patients with a likely indication for thrombectomy to the regional comprehensive stroke center (CSC) based on symptom severity and teleconsultation with a physician. In Stockholm, 44% of patients with prehospital code stroke have stroke mimics. Inadvertent triage of stroke mimics to the CSC could lead to inappropriate resource utilization. Aims To compare the characteristics between (1) triage-positive stroke mimics and stroke (TP mimics and TP stroke) and (2) triage-negative stroke mimics and stroke (TN mimics and TN stroke) and to (3) compare the distribution of stroke mimic diagnoses between triage-positive and triage-negative cases. Methods This prospective observational study collected data from October 2017 to October 2018, including 2,905 patients with suspected stroke who were transported by code-stroke ambulance to a Stockholm regional hospital. Patients directed to the CSC were defined as triage-positive. Those directed to the nearest stroke center were defined as triage-negative. Results Compared to individuals with TP stroke (n = 268), those with TP mimics (n = 55, median 64 vs. 75 years, P < 0.001) were younger and had lower NIHSS score (median 7 vs. 15, P < 0.001). Similarly, those with TN mimics (n = 1,221) were younger than those with TN stroke (n = 1,361, median 73 vs. 78 years, P < 0.001) and had lower NIHSS scores (median 2 vs. 4, P < 0.001). Functional paresis was more common in those with TP mimics than in those with TN mimics, 18/55 (32.7%) vs. 82/1,221 (6.7%), P < 0.001. Systemic infection was less common in those with TP mimics than in those with TN mimics, 1/55 (1.8%) vs. 160/1,221 (13.1%), P < 0.011. There was a trend toward “syncope, hypotension, or other cardiovascular diagnosis” being less common in those with TP mimics than in those with TN mimics, 1/55 (1.8%) vs. 118/1,221 (9.7%), P < 0.055. Conclusions In the SSTS, those with triage-positive and triage-negative stroke mimics were younger and had less severe symptoms than patients with stroke. All patients with TP mimics who had hemiparesis but overall exhibited less severe symptoms against true stroke but more severe symptoms than those with TN mimics were triaged to the nearest hospital. Over-triage of functional paresis to the CSC was relatively common. Meanwhile, a large majority of cases with minor symptoms caused by stroke mimics was triaged correctly by the SSTS to the nearest stroke center.